(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2023)
In this research we studied the impact of capital structure represented with two independent variables(return on assets-ROE, Return on equity ROE We implemented this study on the commercial banks in Syria, we used the descriptive method to study our variables, then we used statistics method to find the impact of capital structure on financial performance using (EVIEWS) program, we found that there is significant relationship between the independent variables and the return on assets and return on equity, and we can explain this result by the ability of commercial banks in Syria to make profits out of their own money, regardless the way assets of these banks were financed, and their ability to manage its assets in good way, and use it in investment activities to increase their profitability